WRITING FOR PUBLICATION AS A TOOL FOR TEACHERS’ PROFESSIONAL DEVELOPMENT - Hartini, Nurani; Hendriwanto (Cirebon International Conference on Education and Economics Proceeding, 2024)
The present study was aimed to explore the teachers experiences in writing for publication as a platform for teacher professional development. The six participants were recruited to participate in writing scholarly article. The data were gained from interview and writing draft. The findings showed that the integration of writing for publication in the program of teacher professional development was an effective ways to improve teachers’ competence. Most teachers of the participant argued that the platform of writing for publication gave them the benefit of professional input. Through writing for publication, they had a chance to reflect their instructional practices, design the qood quality in teaching, and share knowledge with the wider community.